Antibacterial, Antibiofilm, and Efflux Pump Inhibitory Properties of the Crude Extract and Fractions from Acacia macrostachya Stem Bark - Akua Frema Barfour; Abraham Yeboah Mensah; Evelyn Asante-Kwatia; Cynthia Amaning Danquah; Daniel Anokwah; Silas Adjei; Michael Kwesi Baah; Merlin L. K. Mensah (The Scientific World Journal)
Microbial infections remain a public health problem due to the upsurge of bacterial resistance. In this study, the antibacterial, antibiofilm, and efflux pump inhibitory activities of the stem bark of Acacia macrostachya, an indigenous African medicinal plant, were investigated. In traditional medicine, the plant is used in the treatment of microbial infections and inflammatory conditions. A crude methanol extract obtained by Soxhlet extraction was partitioned by column chromatography to obtain the petroleum ether, ethyl acetate, and methanol fractions. Antibacterial, efflux pump inhibition and antibiofilm formation activities were assessed by the high-throughput spot culture growth inhibition (HT-SPOTi), ethidium bromide accumulation, and the crystal violet retention assay, respectively. The minimum inhibitory concentrations (MICs) of the crude extract and major fractions ranged from 250 to ≥500 μg/mL. At a concentration of 3.9–250 μg/mL, all extracts demonstrated >80% inhibition of biofilm formation in S. aureus. In P. aeruginosa, the EtOAc fraction showed the highest antibiofilm activity (59–69%) while the pet-ether fraction was most active against E. coli biofilms (45–67%). Among the test samples, the crude extract, methanol, and ethyl acetate fractions showed remarkable efflux pump inhibition in S. aureus, E. coli, and P. aeruginosa. At ½ MIC, the methanol fraction demonstrated significant accumulation of EtBr in E. coli having superior efflux inhibition over the standard EPIs: chlorpromazine and verapamil. Tannins, flavonoids, triterpenoids, phytosterols, coumarins, and saponins were identified in preliminary phytochemical studies. Stigmasterol was identified in the EtOAc fraction. This study justifies the use of A. macrostachya in the treatment of infections in traditional medicine and highlights its potential as a source of bioactive compounds that could possibly interact with some resistance mechanisms in bacteria to combat antimicrobial resistance.